Can LI-RADS imaging features at gadoxetic acid-enhanced MRI predict aggressive features on pathology of single hepatocellular carcinoma?. Issue 132 (November 2020) - Wei, Hong; Jiang, Hanyu; Liu, Xijiao; Qin, Yun; Zheng, Tianying; Liu, Siyun; Zhang, Xin; Song, Bin
Highlights: LI-RADS imaging features can be used as biomarkers for predicting aggressive pathologic features and recurrence of HCC. Tumor size > 5 cm and absence of nodule-in-nodule architecture were independent predictors of microvascular invasion. Enhancing capsule and corona enhancement were independent predictors of high-grade HCCs. Blood products in mass, corona enhancement, and serum AFP level > 400 ng/mL are associated with recurrence of single HCC. Abstract: Purpose: To investigate whether Liver Imaging Reporting and Data System (LI-RADS) imaging features at preoperative gadoxetic acid-enhanced MRI can predict microvascular invasion (MVI) and histologic grade of hepatocellular carcinoma (HCC) and to evaluate their associations with recurrence after curative resection of single HCC. Materials and methods: From July 2015 to September 2018, 111 consecutive patients with pathologically confirmed HCC who underwent gadoxetic acid–enhanced MRI within 1 month before surgery were included in this retrospective study. Significant MRI findings and clinical parameters for predicting MVI, high-grade HCCs and postoperative recurrence were identified by logistic regression model and Cox proportional hazards model. Results: Twenty-six of 111 (23.4 %) patients had MVI and 36 of 111 (32.4 %) patients had high-grade HCCs, whereas 44 of 95 (46.3 %) patients experienced recurrence. Tumor size > 5 cm (OR = 9.852; p  < 0.001) and absence of nodule-in-nodule architecture (OR = 8.302; p  = 0.001) were independent predictors of MVI. Enhancing capsule (OR = 4.396; p  = 0.004) and corona enhancement (OR = 3.765; p  = 0.021) were independent predictors of high-grade HCCs. Blood products in mass (HR = 2.275; p  = 0.009), corona enhancement (HR = 4.332; p  < 0.001), and serum AFP level > 400 ng/mL (HR = 2.071; p  = 0.023) were independent predictors of recurrence. Conclusion: LI-RADS imaging features can be used as potential biomarkers for predicting aggressive pathologic features and recurrence of HCC. The identification of prognostic LI-RADS imaging features may facilitate the selection of surgical candidates and optimize the management of HCC patients.